Monthly Comments - Hart, Ansell (My University, 1961)
Comments in memory of Richard Pitt Pierre who was a sound lawyer of great integrity
4 pgs. Typescript, sepia-toned, in good condition.
Keywords: Kingston (Jamaica) - History - Periodicals; Hart Ansel 1878-